Strategies towards Orthopaedic Tissue Engineered Graft Generation: Current Scenario and Application - Mallick S.P.; Beyene Z.; Suman D.K.; Madhual A.; Singh B.N.; Srivastava P. (My University, 2025)
Even though degradation and damage to bone and cartilage tissue can be resolved naturally, but there is a great challenge to regenerate functional tissue due to multiple pathological conditions. To treat the diseased/ damaged bone and cartilage tissue as well as to improve or maintain its natural functions and structure, there are different strategies being developed for repair and regeneration of these tissues. Various innovative researches lead to remarkable improvement in clinical outcome of defective bone and cartilage treatments. Biomaterial based scaffolds which are capable of supporting cell growth and applied for replacement of tissue in vivo for both bone and cartilage. The review also delineates about the tissue engineering bioreactors for the recreation of frameworks to recellularise the graft in vitro by presenting them to physiologically significant mechanical or potentially hydrodynamic stimulation condition. This review summarizes and discusses the strategies for regeneration and repair of bone and cartilage tissue, current scenario and application. © 2019, The Korean Society for Biotechnology and Bioengineering and Springer.